Aquinas on Temperance. (11th October 2017) - Chua, Reginald Mary
Abstract: The purpose of this essay is to explore, and clarify, some key features in Aquinas' account of the virtue of temperance, with an eye to answering some common objections raised against a positive evaluation of temperance. In particular, I consider three features of Aquinas' understanding of temperance: First, the role of the rational mean in temperance; second, the role of rightly ordered passions in temperance; and third, the 'despotic' control of reason over the passions in temperance. Along the way I consider three common objections to Aquinas' account of temperance: the objection that temperance can be misused for evil, the objection that temperance devalues effort, and the objection that temperance devalues strong passions and thereby implicitly devalues the goodness of sexuality. In responding to these objections on behalf of Aquinas, I take the opportunity to clarify and slightly extend Aquinas' account of temperance.